Mitochondrial epigenetic mechanisms in cancer: an updated overview - Stoccoro, Andrea; Coppedè, Fabio (Frontiers in Cell and Developmental Biology, 2026)
Mitochondria are central organelles in regulating apoptosis, cellular metabolism, metabolite biosynthesis, energy production, and overall cellular homeostasis. Over the past years, abundant evidence has shown that mitochondrial dysfunction and the resulting metabolic reprogramming profoundly influence key hallmarks of tumor development, including initiation, progression, angiogenesis, and metastasis, playing a role also in therapeutic resistance. Consequently, mitochondria have emerged as a promising target for anticancer therapy. Beyond well-known mutational abnormalities in the mitochondrial genome, recent studies indicate that altered mitochondrial epigenetic mechanisms could also contribute to cancer etiology. In the current review, we present a brief, up-to-date overview of the literature on mitochondrial epigenetic regulation in cancer. We will focus on the main characterized mitoepigenetic mechanisms, namely mitochondrial DNA (mtDNA) methylation and activity of mtDNA-encoded non-coding RNAs. We also consider bidirectional epigenetic crosstalk between the nucleus and mitochondria, whereby metabolites and signaling pathways coordinate chromatin states and mitochondrial function. Collectively, available evidence links mitoepigenetic alterations to tumor progression and pharmacoresistance, nominating these pathways as tractable targets for pharmacological intervention.